A compact metamaterial structure with dual-planar meander line (DML) patterns. (28th February 2018) - Xu, Xiaofei; Wang, Yefang; Wei, Juzheng
Abstract: A compact metamaterial element structure is proposed which is characterized with dual-planar meander line (DML) patterns. Compared with existing single planar solutions, the new design is with an extremely reduced resonance frequency. Good agreement is observed between the simulated and measured results. To strengthen the compacting effect, the effective material properties are further retrieved and compared. By calculating the ratio of resonator size to resonating wavelength, the proposed DML design is featured with a deep subwavelength element size at the order of 1/30 wavelength. We remark that this compacting effect does not sacrifice the functional bandwidth of negative permittivity. The negative permittivity bandwidth for the DML design is nearly 70%, much larger than those of existing single planar structures. By utilizing more advanced fabrication technology, the DML element size can be further decreased if the meander lines are made thinner in future.